Lietuvių kalbos būdvardžiai su priesaga *-u̯o- - Ambrazas, Saulius (Baltistica, 2008)
ADJECTIVES WITH THE SUFFIX *-u̯o- IN LITHUANIANSome Lithuanian deverbal adjectives with the pure suffix -vas (-a), based on the stem u / eu / ou (cf. Lith tę́vas, Latv tiêvs ʽthinʼ, Corn tanow ʽthin, gracefull; softʼ, Gk τανα(ϝ)ός ʽstretched, long; thinʼ and OInd tanúḥ ʽthin, flabby, frail, weak, insignificantʼ, OChSl tьnъ-kъ ʽthinʼ, Lat tenuis ʽthin, leanʼ), came fromLate Proto-Indo-European, cf. Lith gývas (-à) and Latv dzîvs, OPruss gijwans (lebendigen) III 437, Slav *živъ, Lat vīvus, OInd jīváḥ ʽlive, livingʼ : I-E *gu̯ei- / gu̯ī- ʽto live, becomeʼ.This derivational type is unproductive in Lithuanian. However the new extended suffix -s-vas (-a) was formed in Lithuanian, cf. Lith gel̃svas (-à) ʽyellowishʼ : gel̃sta ʽturns yellowʼ.Lithuanian substantival adjectives with the extended suffix -y-vas (-a) have some derivational parallels in other Indo-European languages, cf. Lith ankstývas (-a) : ankstùs (-ì) ʽearlyʼ, akývas ʽsharp-sighted, vigilant; frank, visual, evidentʼ : akìs ʽeyeʼ and OChSl gladivъ ʽhungryʼ : gladь ʽhungerʼ, Lat statīvus ʽstandingʼ : statio, status ʽcondition, state, standingʼ, and OInd rājīva- ʽstripedʼ : rājī́- ʽstripeʼ.
Keywords: lietuvių kalba; būdvardis